An Asian Perspective on Chiara Lubich and her Pedagogy of Fraternity: An Example of the Course "Culture of Unity" in Higher Education in Taiwan - Sonja Mei Tin Huang (Nicolaus Copernicus University in Toruń, 2019)
As founder of the Focolare Movement, Chiara Lubich was greatly influenced by various fields and disciplines. Her thinking offers a platform of common ground for dialogue. The fundamental elements of Chiara's dialogue are the concepts of love and fraternity, which not only help the Catholic Church to have dialogue with other cultures and religions, but are also relevant to the academic world and our daily life. Chiara's thoughts on unity offer a fresh new perspective; once we have adapted our thinking to this, then a new kind of education becomes possible. Her spirituality of unity-introduced to Asia in 1966-has been influential despite the fact that most of the population are non-Christian. Recently, some Asian scholars have been exploring new approaches using Chiara's philosophy to improve their research methodology and teaching; in Taiwan, the "Culture of Unity" course has experimented with new educational techniques influenced by Chiara's thinking. This paper aims to examine Chiara's thoughts on education, as well as her influence on higher education in Taiwan.